Two children with rapid onset obesity combined with respiratory and endocrine dysfunction. do they have ROHHAD?. (24th May 2012) - Lucas-Herald, AK; Davidson, M; Davies, P; Donaldson, MC; McNeill, E; Morrison, J; Shaikh, MG
Abstract : We present two children with rapid onset obesity presenting to hospital with acute respiratory failure requiring admission to paediatric intensive care within a week of each other. The first case is a Caucasian girl who had exhibited hyperphagia and food stealing behaviour from the age of 17 months. Aged three years old, she suffered a respiratory arrest in hospital where she was admitted with acute renal failure. At this point, she weighed 32 kg (BMI 22 kg/m 2, 3.4 SDS). Investigations revealed hyperprolactinaemia (8087 mu/l), a failed growth hormone (GH) stimulation test (peak 0.2 ug/l) and hypernatraemia (184 mmol/l). The second case, a British Pakistani boy, with no family history of consanguinity, weighed 33 kg at 2 years of age, (BMI 29 kg/m2, 4.9 SDS). Aged 3, he has already experienced two respiratory arrests secondary to minor lower respiratory tract infections. Respiratory sleep studies showed a mixed pattern with both central and obstructive sleep disordered breathing for both children. Both cases are now established on overnight BIPAP ventilation. A diagnosis for both children of ROHHAD syndrome (Rapid Onset Obesity with Hypoventilation, Hypothalamic and Autonomic Dysfunction) has been suggested. First described in 2000, ROHHAD is extremely rare with only 75 cases documented in the literature. Suggested diagnostic/descriptive criteria for ROHHAD syndrome include alveolar hypoventilation plus >1 of the following: rapid onset obesity, hyperprolactinaemia, disordered water balance, central hypothyroidism, failed GH stimulation test, corticotrophin deficiency and delayed/precocious puberty. Both children demonstrate several of these criteria (table 1 ). ROHHAD is associated with the development of neural crest tumours and with potentially fatal respiratory arrests. Management of ROHHAD is largely supportive but includes monitoring for tumours. We discuss whether both of these children who presented within a few weeks of each other have this rare condition of ROHHAD.